Differential Proteomic Analysis of Date Palm Leaves Infested with the Red Palm Weevil (Coleoptera: Curculionidae) - Rasool, Khawaja Ghulam; Khan, Muhammad Altaf; Tufail, Muhammad; Husain, Mureed; Mehmood, Khalid; Mukhtar, Muhammad; Takeda, Makio; Aldawood, Abdulrahman Saad (2018)
The red palm weevil, Rhynchophorus ferrugineus (Oliv.) (Coleoptera: Curculionidae), is a highly damaging pest of palm trees worldwide. The infestation is highly concealed in nature. Hence, a highly sensitive and reliable early detection technique needs to be applied in the field for identification and treatment of the infested date palms to curtail further infestation. We have recently reported the differential proteomic analysis of the date palm stem tissues associated with the red palm weevil infestation. In this study, we examine the response of date palm infested with red palm weevil based on the leaf proteome expression changes detected using two-dimensional differential gel electrophoresis (2D-DIGE) followed by Matrix-Assisted Laser Desorption/Ionization-Time-of-Flight (MALDI-TOF). We observed qualitative and quantitative proteome differences between the control and weevil-infested date palm samples. The red palm weevil infestation induced specific responses attributable to weevil feeding, relative to artificially wounded trees (which were used as a control). Differential proteomics led to the identification of 32 red palm weevil infestation-specific protein spots (P ≤ 0.05 having ≥ 1.5-fold modulation) that were further subjected to mass spectrometer analysis for identification and characterization. Proteins involved in plant stress and plant defense, photosynthesis, carbohydrate utilization, and protein degradation were affected in infested plants. The differentially expressed red palm weevil infestation-specific peptides can be used as biomarkers for the identification of early infestation with this insect in date palm trees. Moreover, our study demonstrates the potential use of proteomic strategies in diagnosing phyto-infestation caused by insect pests, diseases, and perhaps even for variety selection.